PENGGUNAAN WAJAH MANDRA SEBAGAI STIKER WHATSAPP MENURUT UNDANG-UNDANG HAK CIPTA: The Use Of Mandra's Face As Whatsapp Stickers According To Copyright Law - Lady Vera Verev; Aline Gratika Nugrahani (Faculty of Law, Universitas Trisakti, 2025)
WhatsApp is a communication platform that allows users to share messages, images, videos, GIFs, and stickers in the digital era. One of the most popular features among users is the use of stickers or GIFs that feature the faces of public figures. A common example in Indonesia is the use of a sticker with the portrait of actor Mandra, particularly a scene from the comedic television series Si Doel Anak Sekolahan, accompanied by the text